Dynamic simulation and optimization of a novel energy system with Hydrogen energy storage for hotel buildings - Farrokhi, Meysam; Javani, Nader; Motallebzadeh, Roghayyeh; Ebrahimpour, Abdolsalam (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
In the current study, an innovative smart energy system based on hybrid solar-GT energies is proposed. Transient performance assessment and techno-economic analyses are conducted to evaluate the dynamic performance of the system. The system has three main parts: solar panels, a Hydrogen production and storage system and gas turbine system, a chiller, and several heat exchangers and auxiliary components. The goal is to set a stand-alone system to generate the need of the building, including heating, power, and cooling. The system is an off-grid system due to its energy storage system. The system is analyzed comprehensively from 3E standpoints. A parametric study of key design variables is performed, and optimization is carried out to find the best solution point. Results indicate that at the optimized point, the system reaches the effectiveness of 39.5%, the emission of 0.85 kg/kWh and the Levelized product cost of 0.051 $/kWh. Furthermore, increasing the pressure of the (absorption chiller) AC in the (gas turbine) GT cycle from 1.5 to 7.5 results in a sharp decline in net output work. (c) 2022 Elsevier Ltd. All rights reserved.
Keywords: Hotel building; Dynamic simulation; Renewable energies; Optimization; Hydrogen energy storage; MULTIOBJECTIVE OPTIMIZATION; GAS-TURBINE; EXERGY; CONFIGURATIONS; PERFORMANCE; Thermodynamics; Energy & Fuels